2021
DOI: 10.4081/aamr.2021.149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of adverse events following immunisation among children less than 24 months attending immunisation clinics in Kano, Nigeria

Abstract: Adverse Events Following Immunisation (AEFI) contribute to child morbidity and mortality as they often lead to low uptake of vaccines with consequent persistence of vaccine-preventable diseases. It is essential to assess the prevalence of AEFIs in northern Nigeria, where misconceptions about immunisation exist. This study assessed the prevalence and pattern of AEFI among children less than 24 months after attending immunisation clinics in Kano, Nigeria. Using a mixed-methods design, adapted intervieweradminist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
2
0
2
Order By: Relevance
“…This study found a generalized/systemic presentation to be the most common site of AEFIs reported by mothers and the pentavalent vaccine to be the vaccine most often believed to be the cause of AEFIs. The finding regarding generalized presentation is consistent with earlier studies [ 13 , 15 17 ]. The finding that the pentavalent vaccine was the most frequently cited cause of an AEFI is also not unexpected since it is a combination of 5 vaccines in a single dose and has been reported to be associated with increased incidence of AEFIs and due to the diphtheria, pertussis, and tetanus (DPT) components of the pentavalent vaccine [ 13 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study found a generalized/systemic presentation to be the most common site of AEFIs reported by mothers and the pentavalent vaccine to be the vaccine most often believed to be the cause of AEFIs. The finding regarding generalized presentation is consistent with earlier studies [ 13 , 15 17 ]. The finding that the pentavalent vaccine was the most frequently cited cause of an AEFI is also not unexpected since it is a combination of 5 vaccines in a single dose and has been reported to be associated with increased incidence of AEFIs and due to the diphtheria, pertussis, and tetanus (DPT) components of the pentavalent vaccine [ 13 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…The finding regarding generalized presentation is consistent with earlier studies [ 13 , 15 17 ]. The finding that the pentavalent vaccine was the most frequently cited cause of an AEFI is also not unexpected since it is a combination of 5 vaccines in a single dose and has been reported to be associated with increased incidence of AEFIs and due to the diphtheria, pertussis, and tetanus (DPT) components of the pentavalent vaccine [ 13 , 18 , 19 ]. We found fever to be the most common AEFI observed by mothers following the vaccination of their children.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Drowsiness/sleep disturbance was observed only at 6 weeks and 14 weeks. The current study reports more diverse and higher incidences of AEFIs as compared to previous studies that mainly report fever, redness swelling and excessive crying (9)(10)(11). While most others studies have observed AEFIs at single immunization event, present study reports vaccine related problems during primary immunizations among the children followed through and up to nine months.…”
Section: Discussioncontrasting
confidence: 46%